Studi Eksplorasi Tanaman Obat Asli Indonesia Di Kabupaten Manggarai Dan Manggarai Barat Provinsi Nusa Tenggara Timur: Menggali Kearifan Lokal Suku Manggarai - Husin Rayesh Mallaleng (2020)
Indonesia is experiencing a disease epidemiological transition, from an infectious disease to a non- communicable disease. Therefore it is necessary to guarantee public services provided by the Regional Government to the community where the community is given the widest possible opportunity to develop, improve and use health services that are accountable for their benefits and safety, are of quality, fast, easy, affordable, and measurable. One of them is traditional health services made from ingredients. The study was conducted on 03 s.d. December 7, 2018 with the research subject is the Manggarai Tribe in Manggarai and West Manggarai Regencies, Flores, East Nusa Tenggara. The data was collected using the exploratory survey method and the participatory rural appraisa method. From exploration in Manggarai Regency and West Manggarai Regency, East Nusa Tenggara, 19 (nineteen) types of medicinal plants used by the Manggarai community were found. Most of the plants found in the previous study were already at UPT Materia Medica, but there are some medicinal plants that are the same, it's just different varieties, for example kalakode or forest betel (Piper betle var. Siribosa), muscle greges (Equisetum debile), red lemongrass (Cymbopogon citratus), forest basil (Ocimum sp.). These plants also have different uses between Manggarai and Java. All medicinal plants found will be planted at UPT Materia Medica Batu, except for Akway (Drimys piperita) which is brought in the form of simplicia.